AN INVESTIGATION OF COHESIVE DEVICES ON READING COMPREHENSION TEXTS IN ONLINE MEDIA - Virgi Marlany Ibnatul Karimah; Didin Nuruddin Hidayat (English Education Study Program Faculty of Teacher Training and Education, 2021)
The objective of this research is to analyze reading comprehension text's cohesion devices from online media. This research is descriptive qualitative research. The sample of this research is reading comprehension texts from ESL Lounge and British Council. The data were gathered using data and collection technique by Lodico (2006) and were analyzed using Halliday and Hasan's (1976) theory. The findings showed that the dominant grammatical cohesion devices of both websites are references. In contrast, the dominant lexical cohesion devices on both websites are repetition. Further, the dominant grammatical cohesion in ESL Lounge is to justify the writer's position and interact with their readers. Meanwhile, in the British Council, demonstrative references refer to the particular object. The lexical cohesion repetition aims to concentrate the ideas and avoid the readers becoming confused in recognizing the terms in the text.